Impact of institutional credit on agricultural productivity in India: A time series analysis - P, SHIVASWAMY G; J, RAGHAVENDRA K; R, ANUJA A; SINGH, K N; T, RAJESH; V, HARISH KUMAR H (The Indian Journal of Agricultural Sciences, 2020)
The institutional credit has always been perceived as a critical factor for agricultural development in India through complementing working capital, easing liquidity and investment constraints. The present study has examined the trends and regional variations in institutional credit flow to agriculture in India for the period 1991–92 to 2016–17 using compound annual growth rate. Further, impact of institutional credit on agricultural productivity was also assessed using panel data regression. The study is based on the secondary data collected from various published sources. Results indicated that institutional credit to agriculture in real terms has registered a significant positive growth during the past four decades and the highest annual growth was observed during 2001–02 to 2010–11. Scheduled commercial banks have emerged as the dominant source of agricultural credit. However, cooperative banks are still the major sources of production credit. Regional analysis showed that southern states had access to highest production and investment credit per hectare, while eastern and northeastern states had the least credit outreach per hectare. Panel data regression model testified that institutional credit has a significant and positive impact on agricultural productivity. Therefore, the study has suggested for better access to credit of smallholders especially in eastern, western and north eastern states through simplification of procedures.